Case report: Chest radiotherapy-induced vertebral fractures in lung cancer patients: a case series and literature review - Oscar Arrieta; Francisco Lozano-Ruiz; Alberto Guijosa; Pamela Soberanis-Pina; Monika Blake-Cerda; Ana Pamela Gómez-García; Federico Maldonado-Magos; Emilio Conde-Flores; Andrés F. Cardona; Sandra Ileana Pérez Álvarez; Luis Antonio Cabrera-Miranda (Frontiers in Oncology)
BackgroundAs survival rates for lung cancer (LC) patients continue to rise, the adverse impacts of therapies become more relevant. Radiotherapy is known to negatively affect bone health. However, radiotherapy-induced vertebral fractures in lung cancer patients remain an exceedingly rare and underrecognized condition that could be mistaken for bone metastasis.Case presentationWe identified three LC patients (all long-term survivors), aged 67 to 81, who developed thoracic vertebral fractures post-chest radiotherapy, within irradiated fields; two had advanced non-small cell lung cancer (NSCLC) and one had extensive small cell lung cancer (SCLC). Baseline imaging confirmed that the fractures occurred after therapy. The median time from radiotherapy to fracture onset was 19 months (range: 1-30 months), with a median follow-up time from the initial fracture of 39 months (range: 37-61 months). All observed fractures were compressive in nature. These patients shared common characteristics, including advanced age, a history of heavy smoking, and high radiation doses. Additionally, hypermetabolic activity at the fracture sites necessitated MRI to differentiate these fractures from bone metastases. Management involved interventional strategies such as vertebroplasty, kyphoplasty, and rhizotomy, along with general and pharmacological measures to prevent subsequent fractures.ConclusionsDespite their low incidence, radiotherapy-induced vertebral fractures in LC patients are clinically significant and may resemble bone metastases on PET-CT imaging. MRI, alongside risk factors similar to those of osteoporosis, can facilitate prompt identification and differentiation. As survival rates in LC patients improve, the relevance of this adverse effect increases, underscoring the need for implementing bone protective strategies to further enhance patient outcomes and quality of life.